Strategi Pemasaran Digital: Inovasi untuk Maksimalkan Penjualan Produk Konsumen di Era Digital - Andirwan, Andirwan; Asmilita, Virda; Zhafran, Muhammad; Syaiful, Andi; Beddu, Megawati (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This research focuses on Digital Marketing Strategies to Increase Consumer Product Sales in the Digital Era. The findings highlight the positive role of digital marketing strategies, such as online advertising campaigns and consumer data analysis, in boosting sales. Technology Acceptance Theory and the Consumer Behavior Model are utilized to understand consumer responses. The results indicate that TAM concepts, like usefulness and ease of use, significantly influence consumer acceptance of online advertising campaigns. By understanding the consumer journey stages and personalizing messages, companies can create relevant customer experiences. Consumer data analysis helps companies stay competitive in the evolving digital market. The research conclusion emphasizes the need for continuous adaptation to technology and consumer behaviour for company success in the digital era.